Influence of puberty stage in immune-inflammatory parameters in well-trained adolescent soccer-players, following 8-weeks of pre-seasonal preparation training - Marios Hadjicharalambous; Eleanna Chalari; Nikolaos Zaras (Exploration of Immunology)
Aim: The immune system can experience temporary suppression following acute or prolonged strenuous exercise, potentially increasing susceptibility to infections. Young athletes, who must balance school, training, studies, and social life, may further disrupt their immune-inflammatory responses. This study aimed to investigate the effects of an 8-week pre-season training on circulating leukocyte responses in well-trained adolescent soccer-players at different stages of puberty. Methods: Thirty-six soccer players, divided into two groups based on their biological age-under sixteen (U16) and above sixteen (A16)-underwent two rounds of assessments. These included evaluations of anthropometrics, physical fitness, and immune parameters before and after an 8-week pre-season soccer training program. Results: No significant treatment or interaction effects were found for erythrocyte sedimentation rate (ESR), platelets, total leucocyte count, immune inflammation markers (IIM), weekly rating of perceived exertion, body composition, sit-and-reach flexibility, or VO2max (P > 0.05). However, post-intervention neutrophil counts were increased, while lymphocyte counts decreased, and IIM levels rose in both groups (P < 0.05). Neuromuscular explosiveness and strength endurance were significantly higher in the A16 group compared to the U16 group (P < 0.05). Body fat was reduced, and all physical fitness parameters improved in both groups over time (P < 0.05). Conclusions: The 8-week soccer-specific training program did not lead to different effects on immune-inflammatory parameters between youth soccer players at different stages of puberty. However, training adaptations, including improvements in physical fitness, were observed in both groups. This suggests that when the same training load (frequency, duration, intensity) is applied to adolescents at different stages of puberty, immune-inflammatory responses are not significantly influenced by age, but physical fitness improves regardless of puberty stage. A key limitation of this study is the lack analysis of lymphocyte subpopulations, which could provide a deeper understanding of the cellular effects of training on immune function.